Oral Perampanel for the Treatment of Super-Refractory Status Epilepticus - Abdallah Rahbani; Grace Adwane; Najo Jomaa (Case Reports in Neurological Medicine)
A 72-year-old man presented with a super-refractory partial status epilepticus following evacuation of a right subdural hematoma. He failed to respond to treatment with high doses of intravenous valproic acid, Levetiracetam, Lacosamide, Thiopental, and Midazolam. He was given 4 mg of Perampanel orally via nasogastric tube and the dose was rapidly increased to 8 mg after 12 hours with cessation of clinical and electrical seizures. Other antiepileptic drugs were tapered progressively with an excellent clinical outcome.